2018
DOI: 10.23889/ijpds.v3i1.448
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Cases of Sleep Disorders through International Classification of Diseases (ICD) Codes in Administrative Data

Abstract: ObjectivesPrevalence, and associated morbidity and mortality of chronic sleep disorders have been limited to small cohort studies, however, administrative data may be used to provide representation of larger population estimates of disease. With no guidelines to inform the identification of cases of sleep disorders in administrative data, the objective of this study was to develop and validate a set of ICD-codes used to define sleep disorders including narcolepsy, insomnia, and obstructive sleep apnea (OSA) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…53 This electronic medical record search was conducted automatically with use of the University of Michigan's Data Direct program. 54 Specifically, we included diagnostic codes used for billing purposes in the ambulatory environment within 2 years prior to COVID-19 admission to best approximate the methodology used by Jolley and colleagues 55 that validated billing codes against sleep clinic diagnoses.…”
Section: This Observational Study Accessed the Michigan Institute Formentioning
confidence: 99%
See 2 more Smart Citations
“…53 This electronic medical record search was conducted automatically with use of the University of Michigan's Data Direct program. 54 Specifically, we included diagnostic codes used for billing purposes in the ambulatory environment within 2 years prior to COVID-19 admission to best approximate the methodology used by Jolley and colleagues 55 that validated billing codes against sleep clinic diagnoses.…”
Section: This Observational Study Accessed the Michigan Institute Formentioning
confidence: 99%
“…However, an investigation of sleep disorders codes (compared to the gold standard of sleep disorder confirmed by a sleep specialist) demonstrated that ICD-9 sleep disorder codes had a positive predictive value of 89% for confirmed sleep disorders. 55 The negative predictive value of the presence of an ICD-9 sleep disorders code was 16%; therefore, of greater concern is that use of diagnostic codes may not capture all patients with sleep disorders. 55 This limitation takes place on the backdrop of a decreased reporting of sleep related symptoms in racial/ ethnic minorities and the socioeconomically disadvantaged, 68 groups that are disproportionately affected by COVID-19.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Index visits included those discharged to home, either with or without support services (discharge disposition code of “4,” or “5”). To eliminate any potential confounding effects of sleep disorders upon our results, we eliminated any index cases where a sleep disorder was coded in any of the 25 DAD diagnosis positions ( 17 ). Unplanned readmissions were identified as subsequent visits with an admission category of “U” (urgent) in the DAD data set.…”
Section: Methodsmentioning
confidence: 99%
“…The sleep of ICU patients is generally disturbed, and the pattern of sleep disorders is apparently complicated (Kamdar et al, 2012;Boyko et al, 2017;Jolley et al, 2018). Specifically, non-specific sleep disorders, including their subtypes (e.g., insomnia, unspecified sleep apnea, sleep-wake circadian rhythm disorder, parasomnias, and other nonspecific sleep problems) are common problems that affect ICU Abbreviations: AUC, area under curve; CI, confidence Interval; DCA, decision curve analysis; GCS, Glasgow coma scale; ICD-9, International Classification of Diseases, Ninth Revision; ICU, intensive care unit; MIMIC-III, Medical Information Mart for Intensive Care III; OR, odds ratio; ROC, receiver operating characteristic curve; SAPS II, simplified acute physiology score II; SOFA, sequential organ failure assessment.…”
Section: Introductionmentioning
confidence: 99%